Defense Mechanisms Reloaded in the Light of Impaired Personality Functioning: An Attempt of Clarification and Simplification Resulting in the DSQ-22-A for Adolescents - Sarrar, Lea; Goth, Kirstin (Frontiers in Psychiatry, 2022)
With the upcoming ICD-11, the diagnostic guidelines for personality disorders will change fundamentally to a dimensional severity concept, including the evaluation of several domains of personality functioning. Moreover, the lifetime perspective will allow this diagnosis even in early adolescence, providing the opportunity for early detection and intervention. In psychodynamic understanding, defense mechanisms are considered to be a part of the „personality structure“, which is one axis in the related diagnostic system (OPD) and showed great similarities to the concept of personality functioning. The most common inventory to assess defense mechanisms is the Defense Style Questionnaire, especially the DSQ-40, which has unfortunately not been specifically adapted to younger ages yet. Using an age-adapted version of the DSQ-40 with simplified formulations, a thorough empirical item analyses and selection was performed, including a face-validity check of the items by experienced therapists and assessments for item correlations, factor structure, reliability, construct and clinical validity in a german clinical and school sample containing 396 adolescents. Though several improvements, similar problems as reported for the adult DSQ versions concerning face-validity and coherence of the item pairs (2-item-method) to represent the single defense mechansms were obtained. Thus, not all item pairs could be kept and a shortened version DSQ-22-A for adoelescents with good psychometric properties was build. The three resulting defense categories adaptive, neurotic and maladaptive showed acceptable scale reliabilities (.63, .56, .68), sound factor structure and convincing convergent and clinical validity in terms of highly significant correlations with impaired personality structure according to the OPD-CA2-SQ as well as with PHQ-D-depression and somatic symptoms, especially for the maladaptive defense category (.75, .44, .34). Likeweise, the maladaptive defense category differed highly significant (p = .000) and with a large effect size of d = 0.9 standard deviations between adolescents from the school and the clinical sample. The DSQ-22-A can be recommended for use in adolescents for research, diagnostics and therapy planning, especially with regard to personality functioning and structure. Possible fundamental changes concerning some basic operationalizations of the defense mechanisms and the 2-item-method were suggested for international discussion.